2018
DOI: 10.1042/bsr20171366
|View full text |Cite
|
Sign up to set email alerts
|

The effect of earthworm extract on promoting skin wound healing

Abstract: Chronic nonhealing wounds pose a significant challenge to healthcare system because of its tremendous utilization of resources and time to heal. It has a well-deserved reputation for reducing the quality of life for those affected and represent a substantial economic burden to the healthcare system overall. Earthworms are used as a traditional Chinese medicine, and have been applied pharmacologically and clinically since a long time in China. However, there is paucity in data regarding its wound healing effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 34 publications
(34 reference statements)
3
25
1
2
Order By: Relevance
“…The D. claparedii extract also showed better effects in wound healing when compared to another study using earthworm extract (100% v/v). WHP displayed by the earthworm extract was 88.3 ± 2.9% on day 11, whereas 1.0% of PO showed 98.9 ± 0.3% for the same period [ 16 ]. Altogether, these results suggested that 1.0% of D. claparedii ointment showed faster wound healing rate as compared to gamat and earthworm extract.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The D. claparedii extract also showed better effects in wound healing when compared to another study using earthworm extract (100% v/v). WHP displayed by the earthworm extract was 88.3 ± 2.9% on day 11, whereas 1.0% of PO showed 98.9 ± 0.3% for the same period [ 16 ]. Altogether, these results suggested that 1.0% of D. claparedii ointment showed faster wound healing rate as compared to gamat and earthworm extract.…”
Section: Discussionmentioning
confidence: 99%
“…The wound area was measured on days 0, 3, 7, 11, and 14 after the trauma by tracing the wound margin using a transparent film and a graph paper. The wound healing percentage (WHP) was calculated using the following formula [ 16 ]: X = days 3, 7, 11, and 14 of post-trauma.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, Japan, Indonesia and the Far East, earthworms have been used to treat various chronic diseases since 1340 AD 10 . The use of earthworm species as wound healing agent has been reported in various studies [11][12][13][14][15] . The medicinal property of earthworm may vary depending on the species and living environment of that organism [16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, new potential therapeutic interventions in wound healing have focused on growth factors with sustained delivery, and growth factors contained within the wound dressing, and have been highlighted in the field of medical dressings (6)(7)(8)(9)(10). Among numerous growth factors applied in the clinic, epidermal growth factor (EGF) is the first and foremost factor to promote the wound healing (11,12). EGF possesses high-affinity receptors that are expressed by both fibroblasts and keratinocytes, and improves epidermal and mesenchymal regeneration, cell mobility, proliferation and synthesis of the ECM, then consequently facilitate wound healing (13,14).…”
Section: Introductionmentioning
confidence: 99%